Terlipressin versus placebo or noradrenalin in the treatment of hepatorenal syndrome: a systematic review and meta-analysis - Wan, Yue-Meng; Huang, Song-Quan; Wu, Hua-Mei; Li, Yu-Hua; Yin, Hong-Jing; Xu, Ying (Frontiers in Pharmacology, 2024)
Abstract Background: Hepatorenal syndrome (HRS) bears a very poor prognosis with unmet need for safe and effective therapies. This systematic review and meta-analysis aimed to re-assess safety and efficacy of terlipressin versus placebo or noradrenaline for HRS, based on previous randomized controlled trials (RCTs). Methods: PubMed, EMBASE, MEDLINE (OvidSP) and Cochrane registers were searched for trials reporting HRS treatment by terlipressin or noradrenaline. Search terms included: ‘hepatorenal syndrome’, ‘terlipressin’, ‘noradrenaline’, and corresponding synonyms. Comparisons between terlipressin, noradreanaline, placebo and albumin were included. Meta-analysis was conducted for treatment response (both HRS reversal and complete response), mortality and adverse events. Results: 15 RCTs were included, enrolling 1236 HRS patients (type 1: 1166, type 2: 70). Treatment with terlipressin+albumin resulted in significantly higher treatment response than placebo+albumin or albumin alone (risk ratio[RR]:2.75, 95% confidence interval[CI]:1.96 to 3.84; I2=28%, P=0.23; n=6). Noradrenaline was equally effective in treatment response compared to terlipressin (RR:1.19, 95% CI:0.96 to 1.46; I2=16%, P=0.31; n=7), but trials were limited by its non-blind design and small size. Sensitivity analysis showed no survival benefit with terlipressin compared to either placebo (RR:1.03, 95% CI:0.83 to 1.28; I2=0%, P=0.72; n=3) or noradreanline (RR:0.83, 95% CI:0.69 to 1.00; I2=4%, P=0.39; n=7) at 30 days of follow-up. Terlipressin carried higher risk of treatment-related adverse events compared to either placebo (RR:2.92, 95% CI:1.48 to 5.77; I2=0%, P=0.75; n=3) or noradrenaline (RR:2.45, 95% CI:1.37 to 4.37; I2=0%, P=0.92; n=5). Conclusion: Terlipressin is superior to placebo, and comparable to noradreanline in treatment response, but survival benefit is lacking. Noradrenaline, with low certainty, may be a better alternative for HRS.